(untitled) (Historia, 2021)
This book by Annie Leatt is a fascinating insight into the rich and long history of religious activity in South Africa pre- and post-apartheid. The author meticulously investigates the concept of secularism and how often it is misunderstood in the broader South African environment. While the book and the concept at first seem fairly complex, the author does an excellent job in exploring the concept and history of religious activity in South Africa. Moreover, the linkages the author makes between religious entities, traditional authorities and political parties are superbly narrated and tie into the current South African political environment where numerous political leaders still try to appeal to traditional and religious authorities.